Challenges for Food and Nutrition Security in the Americas: Costa Rica and its commitment to sustainability - Jiménez García, Víctor (2017)
As a small nation with high biodiversity and an extensive system of protected areas, Costa Rica will face particular challenges regarding food security over the next few years. Thus, whatever development model the country chooses, it must achieve a compromise between conservation and production (agricultural, energy and so on). Although the country’s malnutrition levels are below 5%, socioeconomic asymmetries - which have been increasing in recent years - put a growing proportion of the population at risk. Costa Rica also has a high disaster risk (due to volcanism, seismicity and climatic events), which is likely to be increased by climate change. Moreover, the country’s population is aging and growing very little in absolute numbers, which is also reflected in the predominance of farmers growing older. It is important to mention that the country relies heavily on food imports, mainly of basic grains, to cover the needs of its population. Food production uses a large amount of imported seed and propagating material, which are often not suited to local conditions, as well as very intensive use of agrochemicals, with negative consequences for health and the environment. Over the next few years, it will be crucial to maintain solid public higher-education and research structures in the agricultural field. Although there is no shortage of water in the country in general, water is unevenly distributed at certain times and between regions. Another important challenge is that overweight and obesity show an increasing and alarming upward trend. A comprehensive approach considering many actors and positions is required to ensure food and nutrition in Costa Rica over the next fifty years. To this end and to be consistent with a long tradition that has earned the country recognition, the government should continue with its policies to conserve protected areas and biodiversity. At the same time, it should increase productivity and yields in land with a clear agricultural vocation. This is important for reducing dependence on imported food in order to meet the basic needs of the country’s inhabitants. In order to achieve broad access to sufficient nutritious food, it is essential to reduce the gaps in the population’s socioeconomic conditions. Production systems should be more environmentally friendly by reducing the use of agrochemicals, and making more and better use of soil, and integrated pest, water resources, waste and residue-management practices. It will also be important to encourage, where possible, the use of local species or those adapted to local conditions, some of which are little known and underutilized, which are important for the diet beyond caloric intake (as a source of micronutrients, vitamins and functional compounds). This requires considering the enormous biodiversity present in the country and encouraging genetic improvement in order to reduce dependence on imported seed and propagation materials, since these were often developed for other climatic and edaphic conditions, as well as different productive systems. It is essential to achieve greater differentiation of products that follow certain quality standards in terms of production, marketing and nutritional value over the next few years, and for this to provide some form of competitive advantage. Prevention and mitigation measures must be taken against disasters that can be caused by specific events (hurricanes, volcanoes, earthquakes, etc.) or climate change. It will be important to continue the construction and maintenance of water collection, storage and supply works to reduce water shortages in particular areas and at specific times. Agricultural activity must be made attractive so that young people choose to remain in the countryside rather than migrating to cities. State funding for research on priority issues for the country must be increased, and incentives created so that the private sector also becomes interested in supporting research. It is also necessary to continue promoting high-level human resource training, preferably at top universities abroad, to promote agricultural research. Likewise, technical and vocational education must be promoted with the participation of various institutions (such as the Instituto Nacional de Aprendizaje, technical and vocational colleges and dual education). The country must consider a wide range of options for agricultural production with a view toward ensuring food and nutrition for its inhabitants. This framework must consider all the (bio)technological options, provided they do not conflict with the environment and health. It is also essential to continue and intensify programs that seek to promote healthy eating habits and encourage physical activity among the population.